2004
DOI: 10.1007/s00442-004-1771-4
|View full text |Cite
|
Sign up to set email alerts
|

Mixed inoculations of a microsporidian parasite with horizontal and vertical infections

Abstract: Mixed infections, where more than one parasite genotype is present in a single host, have been suggested to be an important factor in host-parasite interactions. As the host represents a limited resource, co-infecting parasite genotypes are expected to be under resource competition. Competition will not only modify the survival of the co-infecting genotypes, but is also likely to affect total within-host parasite growth as well as host survival and reproduction. We measured parasite infectivity and spore produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 47 publications
2
27
0
1
Order By: Relevance
“…Theory predicts that the optimal level of virulence depends on the relative frequencies of horizontal and vertical transmission (Ebert & Herre 1996). Although it can be complicated by spatial population structure ( Ferdy 2009), phenotypic plasticity ( Vizoso & Ebert 2005b) or multiplicity of infection ( Vizoso & Ebert 2005a), the general prediction is that vertical transmission of pathogens selects for lower virulence. When viruses are primarily maintained by vertical transmission we would expect selection to favour reduced virulence in order to maximize the virus's basic reproductive number, which is directly dependent on the progeny of the host they are currently infecting and, thus, host fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Theory predicts that the optimal level of virulence depends on the relative frequencies of horizontal and vertical transmission (Ebert & Herre 1996). Although it can be complicated by spatial population structure ( Ferdy 2009), phenotypic plasticity ( Vizoso & Ebert 2005b) or multiplicity of infection ( Vizoso & Ebert 2005a), the general prediction is that vertical transmission of pathogens selects for lower virulence. When viruses are primarily maintained by vertical transmission we would expect selection to favour reduced virulence in order to maximize the virus's basic reproductive number, which is directly dependent on the progeny of the host they are currently infecting and, thus, host fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is genetic variation in D. magna-O. bayeri interactions (Mucklow et al 2004;Vizoso & Ebert 2005a, b) and local adaptation of parasites has been shown for other D. magna parasites (Ebert 1994;Ebert et al 1998), some of these new genotypes may be more resistant to O. bayeri infection than their mothers, and thus uninfected. Since the genetic composition of host populations has been shown to influence prevalence dynamics (e.g.…”
Section: Discussion (A) Diapause Drives Prevalence Cyclesmentioning
confidence: 99%
“…Thus with more frequent warmer and longer summers virulent strains are able to invade and transmit in a dense fish population better than the nonvirulent strains. High growth rates have been previously shown to correlate with virulence in malaria parasites (de Roode et al 2005a,b;Bell et al 2006) and in microsporidian parasites of Daphnia (Ebert & Mangin 1997;Vizoso & Ebert 2005).…”
Section: Discussionmentioning
confidence: 99%